2021
DOI: 10.1111/wej.12677
|View full text |Cite
|
Sign up to set email alerts
|

A contemporary and historical analysis of the trace element composition of sewage sludge in the United Kingdom

Abstract: Sewage sludge is the essential by‐product of wastewater treatment and approaching 100% of the sludge generated in the United Kingdom is recycled to agricultural land. In collaboration with three major Water Utility companies in the United Kingdom, a critical statistical analysis of historical and contemporary sludge quality data was completed to demonstrate the long‐term patterns and improvements in the trace element (TE) content of sludge recycled to agriculture since 1989, and to indicate the current status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…• In the study of Liu et al (2021), the mean Cu concentration has remained relatively static and contemporary concentrations are similar to those observed in the early 1990s.…”
Section: Time Quality Trend Of Sewage Sludgementioning
confidence: 54%
See 1 more Smart Citation
“…• In the study of Liu et al (2021), the mean Cu concentration has remained relatively static and contemporary concentrations are similar to those observed in the early 1990s.…”
Section: Time Quality Trend Of Sewage Sludgementioning
confidence: 54%
“…• Liu et al (2021) reported data from 75 wastewater treatment plants (WWTPs) in the United Kingdom, for the period 1989-2017. Only inorganic compounds (heavy metals mostly) were statically analysed: Zn, Cu, Ni, Pb, Cd, Hg, Cr, Mo, As, Se and F. The study showed that trace element concentrations decreased significantly in response to declining pollutant emissions, demonstrating the environmental benefits of effective source control and cleaner technologies.…”
Section: Time Quality Trend Of Sewage Sludgementioning
confidence: 99%
“…Switzerland) have placed restrictions on the use of biosolid application to land based on the potential impact of persistent pollutants (9,10). However, in the UK, almost all biosolids produced are spread on agricultural land (11). Wastewater treatment systems are designed to primarily remove biochemical oxygen demand, suspended solids, and ammonia.…”
Section: Introductionmentioning
confidence: 99%